Assessment of Dual-Mode and Switched-Channel Models with Experimental Vergence Responses - You Yun Lee; John L. Semmlow; Tara L. Alvarez (Journal of Eye Movement Research)
Controversy exists in the literature regarding the basic neural control structure that mediates convergence responses. This study constructed and simulated two models, the switched-channel feedback model and the dual-mode model consisting of preprogrammed with feedback control. Models were constructed and compared to experimental data. The stimuli consisted of 2 deg and 4 deg vergence steps. Both closed- and open-loop settings were utilized. After parameter adjustment, both models could accurately simulate step responses from subjects having a range of response dynamics. The model with a preprogrammed element required less parameter modification when stimulus amplitude changed. Both models could accurately simulate some attributes of vergence; however, neither model could represent the modifications commonly observed within the transient portion of the vergence response.